2019
DOI: 10.1111/joa.12976
|View full text |Cite
|
Sign up to set email alerts
|

Cervical vertebral body growth and emergence of sexual dimorphism: a developmental study using computed tomography

Abstract: The size and shape of human cervical vertebral bodies serve as a reference for measurement or treatment planning in multiple disciplines. It is therefore necessary to understand thoroughly the developmental changes in the cervical vertebrae in relation to the changing biomechanical demands on the neck during the first two decades of life. To delineate sex‐specific changes in human cervical vertebral bodies, 23 landmarks were placed in the midsagittal plane to define the boundaries of C2 to C7 in 123 (73 M; 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 58 publications
(94 reference statements)
9
27
0
1
Order By: Relevance
“…In addition, somatic growth type has a second period of growth during puberty that is not present in neural growth. In a recent study, growth of the cervical spines in the midsagittal plane revealed the cross‐sectional area of C2 to follow a neural growth type, while C3–C7 follow the somatic growth type (Miller, Hwang, Cotter, & Voreperian, 2019), supporting Scammon's report that growth of the neck is complex and does not reflect a single growth type, but rather a mixed or combination of growth types (Scammon, 1930).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In addition, somatic growth type has a second period of growth during puberty that is not present in neural growth. In a recent study, growth of the cervical spines in the midsagittal plane revealed the cross‐sectional area of C2 to follow a neural growth type, while C3–C7 follow the somatic growth type (Miller, Hwang, Cotter, & Voreperian, 2019), supporting Scammon's report that growth of the neck is complex and does not reflect a single growth type, but rather a mixed or combination of growth types (Scammon, 1930).…”
Section: Introductionmentioning
confidence: 75%
“…For example, the descent of the larynx and positioning of the hyoid bone have been described by the relative position along the cervical spine such that the infant hyoid bone descends from C2 to the adult position when the superior margin of the hyoid body aligns with the C3/C4 junction (Bench, 1963; Boë et al, 2006; Carlsöö & Leijon, 1960; Lieberman, McCarthy, Hiiemae, & Palmer, 2001). A more thorough understanding of the directional growth of the individual cervical vertebrae (e.g., supero‐inferior heights and anteroposterior depths) would enhance assessments on relational growth, particularly since, as noted above, research findings have documented different growth trends and types for C2 versus C3–C7 (Miller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary determinant for epiphyseal closure is timing of puberty and this step marks the end of longitudinal growth of the long bones and vertebrae and the attainment of final height [15,102]. Epiphyseal plate closure does not happen simultaneously in the skeleton and a study of union at the epiphyses at the knee involving young males/females aged 18-18.9 years showed that complete epiphyseal union of the femur, tibia and fibula occurred in males/ females in 12.5%/10%, 0%/10%, and 25%/60%, respectively [20,103,104].…”
Section: Alternative Methods To Measure Skeletal Growthmentioning
confidence: 99%
“…Vertebral bodies also grow via primary and secondary ossification centers, in a process where the vertebrae form shapes that optimize the protection of the spinal cord, aid general mobility and provide support for the head and neck. The vertebral bodies continue changing and adapting via endochondral ossification into adulthood as greater mobility and stability is required [20].…”
Section: Bone Modelling and Remodellingmentioning
confidence: 99%